Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1016/j.amjcard.2010.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Disordered Breathing in Patients With the Brugada Syndrome

Abstract: We investigated breathing patterns and the occurrence of arrhythmias and ST-segment changes during sleep in patients with Brugada Syndrome. Patients with Brugada Syndrome are more likely to die from ventricular arrhythmias during sleep. ST-segment changes have been correlated with risk of SCD. Whether sleep disturbances may contribute to arrhythmogenesis is unknown. Patients with Brugada Syndrome underwent an overnight polysomnography (PSG) with simultaneous 12-lead ECG recording. A control group matched by ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
1
18
0
2
Order By: Relevance
“…1a, b. Sleep has been also reported to be associated with an increased incidence of VF in patients with Br-S [12]. Previous study showed that circadian distribution of VF episodes in Br-S was highest during the night time [17].…”
Section: T-wave Alternansmentioning
confidence: 95%
See 1 more Smart Citation
“…1a, b. Sleep has been also reported to be associated with an increased incidence of VF in patients with Br-S [12]. Previous study showed that circadian distribution of VF episodes in Br-S was highest during the night time [17].…”
Section: T-wave Alternansmentioning
confidence: 95%
“…The Br-S is also influenced by the autonomic system. Previous reports showed that vagal tone activity was increasing rapidly before arrhythmic events in Br-S [11] and sleep has been reported to be associated with an increased incidence of VF in patients with Br-S [12].…”
Section: Introductionmentioning
confidence: 97%
“…Patients and control subjects are the same as in the study of Macedo et al [20]. Subject characteristics have been previously reported.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Macedo and colleagues showed that the prevalence of SDB is higher in Brugada patients compared to controls (45% vs 27% respectively) [20]. …”
Section: Introductionmentioning
confidence: 99%
“…66 However, SDB was a highly prevalent comorbidity in patients at risk for SCD such as Brugada syndrome, hypertrophic cardiomyopathy, or in implantable cardioverter-defibrillator (ICD) recipients. [67][68][69] One cohort facing an enhanced risk of malignant arrhythmic events are patients with chronic heart failure (CHF). 70 SDB is common in CHF and is associated with an impaired prognosis.…”
Section: Ventricular Tachycardiamentioning
confidence: 99%